Highly stretchable transparent Ag nanowire-polyurethane hybrid bilayer electrodes for multifunctional applications - Fang Luo; Seo-Yun Choi; Yewon Lee; Jun-Hyeok Kang; Joon Jang; Hyun-Jung Jung; Seungmin Lee; Ji-Yoon Chae; Han-Ki Kim (Science and Technology of Advanced Materials, 2025)
We developed an Ag nanowire-polyurethane (AgNW-PU) mixed electrode on a PU substrate with an optimized bilayer structure for highly stretchable and wearable strain sensors. In the AgNW-PU mixed composite, PU functioned as a stretchable matrix, preserving the high conductivity and transparency of the AgNW network even under applied mechanical stress. The AgNW-rich bottom layer (25:1) provided an effective conduction path, whereas the PU-rich top layer provided mechanical support and elasticity, improving the durability of the electrode under repeated stretching and bending cycles. With the optimized bilayer (AgNW-PU 100:1/25:1), the AgNW-PU bilayer electrode exhibited a low sheet resistance of 26.3 Ω/square and a high transparency of 86.4%. Compared with the AgNW-PU single-layer electrode, the bilayer electrode exhibited superior stretchability, as confirmed by various applications, such as heater devices, strain sensors, and interconnectors. An optimized AgNW-PU bilayer electrode exhibited heat generation of 90°C with 7 V applied even after 15% stretching. The gauge factor of the optimized electrode increased from 8 to 11.2 even as the bending degree increased from 30° to 90°. The AgNW-PU bilayer electrode also demonstrated potential as a stretchable interconnector for various next-generation electronic applications.